2018
DOI: 10.1002/dmrr.2980
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Tcf712 promoter by high‐fat diet impairs β‐cell function in mouse pancreatic islets

Abstract: An HFD was shown to induce aberrant methylation of the Tcf7l2 promoter in mouse islets, which resulted in diminished gene expression. This study provides an evidence of the association between nutrient consumption and gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…High fat diet was found to epigenetically impact TCF7L2, a transcription factor required for pancreatic β-cell survival ( 84). An experimental study demonstrated that mice treated with high fat diet showed an aberrant methylation at the promoter region of the TCF7L2 in β-cells compared to mice fed with a normal diet (84). Although defects in TCF7L2 were commonly detected in T2DM patients, a subset of non-obese T1DM patients were also found to have the same defect (104).…”
Section: Diet and Epigenetic Interplay In T1dm Pathogenesismentioning
confidence: 99%
“…High fat diet was found to epigenetically impact TCF7L2, a transcription factor required for pancreatic β-cell survival ( 84). An experimental study demonstrated that mice treated with high fat diet showed an aberrant methylation at the promoter region of the TCF7L2 in β-cells compared to mice fed with a normal diet (84). Although defects in TCF7L2 were commonly detected in T2DM patients, a subset of non-obese T1DM patients were also found to have the same defect (104).…”
Section: Diet and Epigenetic Interplay In T1dm Pathogenesismentioning
confidence: 99%
“…Increased DNA Methylation in E-Boxes in Promoter/ Enhancer Areas of Cell Cycle Genes in 1-Year-Old Mice Fed Short-term HFD An HFD has been reported to induce methylation changes in gene regulatory regions in multiple tissues, including pancreatic b-cells (45,46). Therefore, we used a targeted DNA methylation analysis (47) to investigate the DNA methylation pattern of the 21 Myc-targeting cell cycle genes identified in Fig.…”
Section: Myc Recruitment To Cell Cycle Promoters Is Enhanced In Isletmentioning
confidence: 99%
“…We also measured the expression of transcription factors that regulate Gipr and/or Glp-1r expression, namely E2f1, MafA, Nkx6.1, Pax6, Pparγ, and Tcf7l2, and found a significant reduction in the expression of all except MafA when comparing Prlr-/to Prlr+/+ mice (Figure 5f). It is interesting to note that all of these transcription factors have been associated with β-cell adaptation during HFD 43,[57][58][59] , but only E2f1 and Pparγ are known to be downstream of PRLR signaling 60,61 .…”
Section: Discussionmentioning
confidence: 99%